2009
DOI: 10.1080/09603120902795598
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-metal pollution and potential ecological risk assessment of sediments from Baihua Lake, Guizhou, P.R. China

Abstract: Baihua Lake, a man-made reservoir, is one of the five drinking water sources for Guiyang City in China's southwestern province of Guizhou. In the present research, the distribution and accumulation characteristics of heavy metals (Pb, Cd, As, Cu and Zn) for the sediment of this lake were analyzed by examination of 10 recently collected samples. A method based on toxic-response factor was applied to assess the potential ecological risk of these heavy metals to the water body. For comparison, the two sets of ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 20 publications
0
38
1
Order By: Relevance
“…Accordingly, characterization of the sediment quality is crucial prior to dredging to ensure that unnecessary costs are not incurred and that there is limited environmental impact and public acceptance [38]. Unfortunately, it was not possible to obtain comprehensive information regarding the characteristics of the lake sediments in Lake Hongfeng due to its depth and location in a Karst landform [39]. Moreover, Liu et al [40] reported that sediment dredging would cause a temporary risk of water quality deterioration in Lake Taihu.…”
Section: Methods Of Controlling the Release Of Phosphorus From The Sementioning
confidence: 99%
“…Accordingly, characterization of the sediment quality is crucial prior to dredging to ensure that unnecessary costs are not incurred and that there is limited environmental impact and public acceptance [38]. Unfortunately, it was not possible to obtain comprehensive information regarding the characteristics of the lake sediments in Lake Hongfeng due to its depth and location in a Karst landform [39]. Moreover, Liu et al [40] reported that sediment dredging would cause a temporary risk of water quality deterioration in Lake Taihu.…”
Section: Methods Of Controlling the Release Of Phosphorus From The Sementioning
confidence: 99%
“…Due to large-scale production and consumption and lack of regulations, heavy metals such as lead (Pb), zinc (Zn), cadmium (Cd), mercury (Hg), and chromium (Cr) are emitted into the environment in large quantities through wastewater irrigation, solid waste disposal, sludge application, vehicular exhaust and atmospheric deposition [8]. As a result, heavy metals are present in industrial, municipal and urban runoff, and they continuously accumulate in the environment in China [9,10,11,12,13]. Since 2005, health related incidents caused by heavy metal pollution have risen sharply in China, with major accidents attracting nationwide attention [14].…”
Section: Introductionmentioning
confidence: 99%
“…The constant, 1.5, allows us to analyze natural fluctuations in the content of a given substance in the environment, and to detect very small anthropogenic influences (Faiz et al 2009). (Wei 1990) b Metal contents in the Nam Co basin (Li et al 2009) c Metal contents of Tibetan top soils (Sheng et al 2012) The potential ecological risk index method of assessing the risk of heavy metals is the only method that considers both the content and toxic response factors of heavy metals, and is the most commonly employed (Huang et al 2009). The potential ecological risk index is calculated using the following equation (Li et al 2013):…”
Section: Methodsmentioning
confidence: 99%